Pengaruh Konsentrasi dan Lama Perendaman Kolkisin terhadap Karakter Poliploidi pada Tanaman Lili Hujan (Zephyranthes rosea Lindl.) - Vivin Diana Putri; Hanik Faizah; Nirmala Fitria Firdhausi (Pro-Life, 2023)
Zephyranthes rosea Lindl. is one of Indonesia's export commodities. Research on the induction of polyploid Z. rosea to increase sales value by increasing its phenotype is still limited and limited to seed organs. The aim of this research was to determine the effect of colchicine concentration, soaking time, and the interaction of the two on polyploidy characters. Z. rosea root organs were treated with colchicine (0%, 0.025%, 0.05%, 0.075%, and 0.1%) and different soaking time (6 hours, 12 hours, 18 hours, and 24 hours) in this study. The result showed that there was a significant effect of colchicine concentration, soaking time, and the interaction of of the two on leaf length, stomata density, and dry weight while flowering time, leaf width, stomata length, stomata width, fresh weight, and flower color were not significantly affected. The lowest leaf length was produced by 0.1% colchicine (21.392 cm), 6 hours of soaking time (22.693 cm), and the interaction of 0.1% colchicine with 6 hours of soaking time (20.633 cm). The highest density of stomata resulted from 0.025% colchicine (787.247/mm2), 6 hours of soaking time (762.626/mm2), and the interaction of 0.025% colchicine with 24 hours of soaking time (906.566/mm2). The highest dry weight resulted from colchicine 0.075% (16.433 gram), soaking time of 12 hours (16.527 gram), and interaction of colchicine 0.075% with soaking time of 12 hours (19.467 gram). Because there were more polyploid characters which were not significantly affected, the polyploid Z. rosea had not been formed in this study.